Pengembangan Konten Kreatif Berbasis Website sebagai Media Pembelajaran pada Materi Geometri Molekul - Nahadi Nahadi; Hayuni Retno Widarti; Ari Syahidul Shidiq; Wiwi Siswaningsih; Atep Rian Nurhadi; Triannisa Rahmawati; Miarti Khikmatun Nais; Rara Djati Anggraeni; Hasna Athaya Rifa; Rismayanti Chusnul Chotimah; Amara Dwi Ayuni; Lusiana Citra Aphelia; Tanti Oktaviani (Postgraduate, University of Mataram, 2025)
Effective chemistry learning should be designed to actively engage students in various activities that promote deep understanding of abstract concepts, skill enhancement, and positive behavior development. This study aimed to develop creative content based on a website as a learning media for molecular geometry topics. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The study involved 32 students at the high school, 5 educators, and 3 validators. The results show that 100% of the validators stated that the content developed on the website is valid. The developed content aligns with the material concept, and the learning objectives are based on the needs and expected learning outcomes. Feasibility test results indicate that the website meets the criteria for facilities and media quality, aligning with standards for an ideal learning platform. Therefore, it can be concluded that the creative website-based content developed for molecular geometry is highly suitable and can increase students engagement in the learning process and understanding of abstract chemical concepts.